ZOONYMS ARE A SPECIFIC LAYER OF LEXICAL LANGUAGE SYSTEMS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article briefly describes zoonyms, their use, also concepts such as zoolexes and a zoonymic vocabulary are also considered. From what language did the word "zoonyms" originate, besides how important is the role of zoonyms in the field of phraseology and linguoculturology. In the end, zoonyms in three dictionaries are compared, such as Russian, British and American.